1995
DOI: 10.1159/000246530
|View full text |Cite
|
Sign up to set email alerts
|

Human Leukocyte Interferon-Alpha versus Podophyllotoxin in Cream for the Treatment of Genital Warts in Males

Abstract: Background: The incidence of overt genital warts, a common sexually transmitted disease of high prevalence, has been on the rise for the last few years. The infection is caused by several types of human papillomaviruses (HPVs), some of which have been accepted as a factor in the pathogenesis of genital squamous-cell carcinomas. Objective: The aim of this double-blind, placebo-controlled study was to compare and evidence differences in clinical efficacy and tolerance between human leukocyte interferon-α (2 × 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 5 publications
(8 reference statements)
0
30
0
2
Order By: Relevance
“…After screening the titles, 129 articles seemed related to our question. After eliminating the duplicate articles and obviously irrelevant studies by reading the abstracts, 16 full texts [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23] met the predefined criteria for inclusion. We excluded one open label study [20] and 3 studies [21,22,23] which were different versions of the study by Edwards et al [9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening the titles, 129 articles seemed related to our question. After eliminating the duplicate articles and obviously irrelevant studies by reading the abstracts, 16 full texts [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23] met the predefined criteria for inclusion. We excluded one open label study [20] and 3 studies [21,22,23] which were different versions of the study by Edwards et al [9].…”
Section: Resultsmentioning
confidence: 99%
“…Five of them were multicentre [9, 11, 15, 18, 21], 3 compared 5% imiquimod [8,9,10] with placebo and 9 compared 0.5% podophyllotoxin with placebo [11,12,13,14,15,16,17,18,19]. Of the 9 trials in which 0.5% podophyllotoxin was used, 3 used cream or gel preparations, 5 used solution preparations, and 1 used both cream and solution preparations.…”
Section: Resultsmentioning
confidence: 99%
“…Several randomized controlled trials have investigated the impact of adjuvant interferon after surgical ablation of CA [20]. The majority of these trials have found a benefit, which did not always reach the level of statistical significance [16, 17, 21, 22, 23]. The modest impact on the recurrence rates, the route of administration and the relatively high cost prevented interferon to become a routine modality in the treatment of CA.…”
Section: Introductionmentioning
confidence: 99%
“…The aqueous extract of Podophyllum peltatum has showed strong antiviral activity [28] and podophyllotoxin was found to be the most active component in inhibiting the replication of measles and herpes simplex type I virus [29,30]. Podophyllotoxin has also been used as an antiviral agent against human Papilloma virus (HPV) that causes condyloma acuminatum [31] Radioprotection Podophyllum hexandrum extract can arrest the cell division and therefore has the potential to act as radioprotectant.…”
Section: Antiviral Activitymentioning
confidence: 99%